2009
DOI: 10.1086/606060
|View full text |Cite
|
Sign up to set email alerts
|

Salicylates and Pandemic Influenza Mortality, 1918–1919 Pharmacology, Pathology, and Historic Evidence

Abstract: The high case-fatality rate--especially among young adults--during the 1918-1919 influenza pandemic is incompletely understood. Although late deaths showed bacterial pneumonia, early deaths exhibited extremely "wet," sometimes hemorrhagic lungs. The hypothesis presented herein is that aspirin contributed to the incidence and severity of viral pathology, bacterial infection, and death, because physicians of the day were unaware that the regimens (8.0-31.2 g per day) produce levels associated with hyperventilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 53 publications
1
38
0
3
Order By: Relevance
“…84 It has been hypothesized that aspirin contributed to the incidence and severity of viral pathology in the 1918-1919 influenza pandemic. 85 Moreover, treatment with antipyretics increased mortality in animal models of influenza infection. 86 Consistent with this notion, we observed that impaired hemostasis due to either a genetic deficiency of TF or an absence of PAR4 dramatically increased lung hemorrhage and increased mortality in mice infected with H1N1.…”
Section: Roles Of the Coagulation Cascade And Platelets In Mouse Modementioning
confidence: 99%
“…84 It has been hypothesized that aspirin contributed to the incidence and severity of viral pathology in the 1918-1919 influenza pandemic. 85 Moreover, treatment with antipyretics increased mortality in animal models of influenza infection. 86 Consistent with this notion, we observed that impaired hemostasis due to either a genetic deficiency of TF or an absence of PAR4 dramatically increased lung hemorrhage and increased mortality in mice infected with H1N1.…”
Section: Roles Of the Coagulation Cascade And Platelets In Mouse Modementioning
confidence: 99%
“…Even the oral uptake of ASA via the drinking water induced significant protection in these mice [42]. In contrast, especially in humans, the administration of ASA was found to increase IAV-caused disease [57]. Therefore, a profound analysis is necessary prior a general recommendation of ASA as a therapeutic approach for influenza [58].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the attitudes of caregivers and public opinions contribute to side effects [45] that are not Endocrine otherwise attributable to RAI therapy. For example, Table 1 directly compares side effects and risks of RAI therapy to those of ordinary over-the-counter aspirin [46][47][48][49][50][51][52][53][54], in widespread use since 1899: a medication the public considers exemplifying safety. Objective comparison suggests RAI therapy to be far safer than therapy with aspirin.…”
Section: Side Effects and Risks Of Rramentioning
confidence: 99%